Addition of probiotic EM-4 with different concentrations in cultivation media on the growth and survival rate of freshwater pomfret fish (Colossoma macropomum) - Muhammad Ilham Fasya; Nanda Diniarti; Salnida Yuniarti Lumbessy (Universitas Djuanda, 2023)
This study aims to analyze the addition of EM-4 probiotics with different concentrations to the cultivation media on the growth and survival of freshwater pomfret fish (C. macropomum). This research was carried out for 50 days at the Fish Production and Reproduction Laboratory, Aquaculture Study Program, Faculty of Agriculture, Mataram University. The method used was an experiment using a Completely Randomized Design (CRD) consisting of 4 treatments and three replications, namely without the addition of probiotics or control (P1); probiotic EM-4 0.5 ml/L (P2); probiotic EM-4 1.5 ml/L (P3); and probiotic EM-4 2.5 ml/L (P4). Test parameters include absolute weight, absolute length, specific growth rate, survival rate, feed conversion ratio, feed utilization efficiency, air quality, and bacterial density. Data analysis used analysis of variance (ANOVA) at a confidence level of 95%. If the research results show significant differences, further tests use the Duncan Multiple Range Test (DMRT). The research showed that adding EM-4 probiotics to the rearing media at different concentrations could significantly affect (p<0.05) fish survival rate, absolute weight, specific growth rate, feed conversion value, and feed utilization efficiency. The treatment of adding EM-4 probiotics to the maintenance media with a concentration of 1.5 ml/L of air provides the best value for survival rates, growth, FCR, and EPP. It can maintain the quality of the cultivation media in good condition for the growth of freshwater pomfret (C. macropomum).